Potential Impact of Climate Change Analysis on the Management of Water Resources under Stressed Quantity and Quality Scenarios - João Rafael Bergamaschi Tercini (MDPI AG, 2021)
Assuring access to high-quality water for its multiple uses is increasingly difficult and relevant, as climate changes are gradually altering the hydrologic cycle and impacting traditional and well-established techniques of water resource management. This manuscript proposes a methodology to assess the impact of climatic variability in pre-established management rules, using spatially interpolated rain gauged data for two future emission scenarios. With them, water allocation and water quality parameters are simulated for the Piracicaba, Capivari, and Jundiaí watersheds (PCJ watersheds) in São Paulo, Brazil, employing comparisons among scenarios of historical and climate modified hydrological series. Five selected water quality indicators are used to confirm that the introduction of climate variation signals worsens water quality parameters, along with a decrease in the capability to meet water demand. This finding suggests the importance of including climate change impact in similar studies in management plans. The results indicate higher stress levels on the watershed when changes in the hydrological regime are introduced by the future conditions modeled and driven by the regional climate model (RCM). Water availability decreases and water quality deteriorates, indicating that stakeholders must take action to progressively implement stricter control measures to achieve the goals established by the watershed master plan regarding the limits or classification set by the body governing the watershed in question. On average, there was an increase of about four times the amount of river stretches (in kilometres), from 29.6 km to 161.9 km outside the limits of the established framework. The average was taken for all parameters as presented in the discussion.